PERAN PENDIDIKAN AGAMA KATOLIK DALAM MEMBENTUK PERILAKU INTERAKSI SOSIAL MAHASISWA KATOLIK DI KECAMATAN OEBOBO - Masan, Valentinus Kopong; Duka, Gerardus Bernadus; Je’e Maly, Emanuel Inocentius; Bria, Bonafentura Jemmy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of Catholic Religious Education in shaping the social interaction behavior of Catholic students in Oebobo District using a descriptive qualitative approach. The background of this study is the tendency of social dynamics among students that do not fully reflect Christian moral values ​​in everyday social interactions. The study was conducted at several universities and church communities in Oebobo District with 30 key informants consisting of active Catholic students, religious educators, and spiritual mentors. Data were collected through in-depth interviews, participant observation, and documentation of educational activities and church services. The results of the study indicate that Catholic Religious Education plays a significant role in shaping the social interaction behavior of Catholic students. The analysis findings indicate that structured religious education, experiential learning (e.g., social service activities and spiritual retreats), and regular moral guidance from educators and spiritual mentors strengthen the internalization of Christian values ​​such as tolerance, empathy, honesty, and cooperation. The majority of respondents (more than 80%) reported positive changes in how they interact with peers, lecturers, and the wider community after consistently participating in the religious education program. However, challenges arise in consistently practicing values ​​outside of the faith community, particularly when faced with social or academic pressures. This study recommends developing more contextual models of religious learning and strengthening collaboration between educational institutions and church communities to maintain the positive impact of moral education on students' social lives.